2019
DOI: 10.3390/min9040226
|View full text |Cite
|
Sign up to set email alerts
|

Coprecipitation of Co2+, Ni2+ and Zn2+ with Mn(III/IV) Oxides Formed in Metal-Rich Mine Waters

Abstract: Manganese oxides are widespread in soils and natural waters, and their capacity to adsorb different trace metals such as Co, Ni, or Zn is well known. In this study, we aimed to compare the extent of trace metal coprecipitation in different Mn oxides formed during Mn(II) oxidation in highly concentrated, metal-rich mine waters. For this purpose, mine water samples collected from the deepest part of several acidic pit lakes in Spain (pH 2.7–4.2), with very high concentration of manganese (358–892 mg/L Mn) and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Manganese oxides can be observed in different natural forms, including manganese nodules, layers in sediments [1][2][3], hydrothermal alteration products [4], or rock varnish forms [5,6]. These minerals have also been observed abundantly in engineered systems and polluted environments worldwide, including the acid-mine-drainage (AMD)-polluted streams [7][8][9]. Majority of the manganese oxide minerals are brown-black and typically occur as intimately intermixed, fine-grained, poorly crystalline masses or coatings [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manganese oxides can be observed in different natural forms, including manganese nodules, layers in sediments [1][2][3], hydrothermal alteration products [4], or rock varnish forms [5,6]. These minerals have also been observed abundantly in engineered systems and polluted environments worldwide, including the acid-mine-drainage (AMD)-polluted streams [7][8][9]. Majority of the manganese oxide minerals are brown-black and typically occur as intimately intermixed, fine-grained, poorly crystalline masses or coatings [10].…”
Section: Introductionmentioning
confidence: 99%
“…Birnessite is a good ion exchanger and can play an important role in controlling heavy metals and other trace metals in soil and groundwater [10,28]. Several heavy metals and toxic trace elements from the AMD-affected streams and soils can be observed in birnessite and todorokite [9]. In addition, ion-trapping properties of birnessite make it a potential negative electrode material for rechargeable lithium batteries [29][30][31]; further, it can be used as a heterogeneous catalyst [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have identified small and dense crystalline structures in the coatings, mixed with less dense, poorly crystalline or amorphous manganese oxyhydroxides [195]. In coatings of filter media from operating groundwater treatment plants birnessite type MnO x was detected [176,183], while poorly crystalline nature is typical of this MnO x variety [112]. Jones et al [195] also reported the presence of birnessite and manganite in coatings formed on filter media.…”
Section: Coatings Characteristicmentioning
confidence: 95%
“…Various forms of manganese oxide are characterized by different effectiveness of contaminant removal [2], nanowires have almost five times greater maximal adsorption capacity of strontium and caesium than nanostructured microspheres [111]. The adsorption capacity of cobalt, nickel and zinc ions varies significantly among the different MnO x with asbolane having the highest metal-removing potential, followed by birnessite and todorokite, and with manganite showing the lowest adsorption properties [112]. Feng et al [113] have investigated the synthesized manganese oxides and proved that birenssite characterized by the largest surface variable negative charge has bigger adsorption capacity on heavy metals (lead, copper, cobalt, cadmium, and zinc) than cryptomelane, todorokite, or hausmannite.…”
Section: Coatings Characteristicmentioning
confidence: 99%
“…Despite these structural differences, they share similar optical properties [ 23 , 109 ]. Asbolane, a Mn(IV) hydroxide exhibiting a higher oxidation state, lacks a constant molecular formula [ 110 ]. Lithiophorite has been categorized as the third type of Mn oxide, alongside layered and tunnel structures, due to its mixed layer structure [ 111 ].…”
Section: Common Mn Oxides In Natural Environmentsmentioning
confidence: 99%